Suriname : Toward Stability and Growth - Nozaki, Masahiro (Departmental Papers; Departmental Paper, 2009)
This paper analyzes the economic growth and stability in Suriname. The paper highlights that in recent years, the outlook has turned substantively more positive. The favorable external environment and the stability-oriented policies of the Venetian administration have boosted confidence in the economy, leading to increased investment, domestic economic activity, and employment. The recent boom in commodity prices has helped boost growth, while increased gold production and investment in the mineral industry are projected to support continued growth in the coming years.